Religions and the Global Rise of Civilizational Populism - Yilmaz, Ihsan; Morieson, Nicholas (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This books explores the rise of civilizational populism throughout the world, and its consequences. Civilizational populism posits that democracy ought to be based upon enacting the 'people's will', yet it adds a new and troubling dimension to populism's thin ideology: a civilization based classification of peoples and division of society. Today, we increasingly find not conflict between civilizations, but conflict within states over their civilizational identity. From Western Europe to Turkey, and from India and Pakistan to Indonesia, populists are increasingly employing a civilization based classification of peoples in order to define the identities of 'the people' and their perceived enemies. This book is the first to examine civilizational populism as global phenomenon rather than a uniquely Western form of politics. Through a series of case studies, the book examines the role played by religion in forming civilizational identities, but also investigates the often deleterious consequences of civilizational populism entering the political mainstream. Prof. Ihsan Yilmaz is the Research Chair of Islamic Studies at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Melbourne, Australia. He is the author of many books, including most recently published Populist and Pro-Violence State Religion: The Diyanet's Construction of Erdoğanist Islam in Turkey (2022) and Creating the Desired Citizen: Ideology, State and Islam in Turkey (2021). Dr. Nicholas Morieson is a Research Fellow at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Melbourne, Australia, and has previously worked as a lecturer at Australian Catholic University, Melbourne. He is the author of Religion and the Populist Radical Right: Secular Christianism and Populism in Western Europe (2021).
Chapter 1: Religions and the Global Rise of Civilizational Populism -- Chapter 2: Civilizationalism, Religions and Populism -- Chapter 3: Islam and Civilizational Populism -- Chapter 4: Christianity and Civilizational Populism -- Chapter 5: Hinduism and Civilizational Populism -- Chapter 6: Buddhism and Civilizational Populism -- Chapter 7: Judaism and Civilizational Populism -- Chapter 8: Predicament of Civilizational Populism.
Keywords: Religion and politics; Political sociology; Comparative government; Politics and Religion; Political Sociology; Comparative Politics